Solve equation i) $\frac{x}{2} \ -\ \frac{1}{5} \ =\ \frac{x}{3} \ +\ \frac{1}{4}$Andii) $\frac{n}{2} \ -\ \frac{3n}{4} \ +\ \frac{5n}{6} \ =\ 21$

i)

$\begin{array}{l} \frac{x}{2} \ -\ \frac{1}{5} \ =\ \frac{x}{3} \ +\ \frac{1}{4}\\ \\ \\ \\ \frac{x}{2} \ -\ \frac{x}{3} \ =\ \frac{1}{4} \ +\ \frac{1}{5}\\ \\ \\ \\ \frac{3x\ -\ 2x}{6} \ =\ \frac{5\ +\ 4}{20}\\ \\ \\ \\ \frac{x}{6} \ =\ \frac{9}{20}\\ \\ \\ \\ x\ =\ \frac{9\ \times \ 6}{20}\\ \\ \\ x\ =\ \frac{9\ \times \ 3}{10}\\ \\ \\ \mathbf{x\ =\ \frac{27}{10}} \end{array}$

ii)

$\begin{array}{l} \frac{n}{2} \ -\ \frac{3n}{4} \ +\ \frac{5n}{6} \ =\ 21\\ \\ \\ \\ \frac{n( 6) \ -\ 3n( 3) \ +\ 5n( 2)}{12} \ =\ 21\\ \\ \\ \\ \frac{6n\ -\ 9n\ +\ 10n}{12} \ =\ 21\\ \\ \\ \\ \frac{7n}{12} \ =\ 21\\ \\ \\ \\ n\ =\ 21\ \times \ \frac{12}{7}\\ \\ \\ \\ n\ =\ 3\ \times \ 12\\ \\ \\ \mathbf{n\ =\ 36} \end{array}$

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

25 Views

Kickstart Your Career

Get certified by completing the course

Advertisements